Perlindungan Hukum Terhadap Para Pihak dalam Perjanjian Sewa Rahim (Surrogate Mother) Ditinjau dari Perspektif Hukum Positif - Vorty, Vicky Chrisna; Irianto, Kartika Dewi (Universitas Pahlawan Tuanku Tambusai, 2025)
The emergence of the practice of uterine leasing is seen as capable of overcoming infertility problems experienced by husband and wife in order to obtain offspring by leasing a surrogate mother's womb. Although the practice of uterine leasing has been implicitly prohibited, the fact is that the practice is still carried out secretly by the community. The binding in surrogete practice is established based on the surrogate agreement that is considered to be null and void. Of course this impacts on the loss rights to sue each other before certain courts in the case of disputes. Therefore, this lookup used be carried out to discover the reasons of the surrogate mother practice exercise still occurs for its prohibited role as nicely as to see the position of legal protection in the exercise primarily based on Indonesian positive law. The analysis was conducted using a legislative approach (statute approach) and analytical approaches (analytical approach) so that it is convered in the scope of normative law research. The research conducted illustrates that the surrogate mother practice still occurs, because there is no legal basis for prohibiting this behavior. In addition, Legal protection are only there to prevent the surrogate practice, but they do not provide any safeguards to overcome future disputes.